(3eGRb GdYhdeI (B/s - (3WGbI, eMeOs ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2007)
(3gPG GdcJGH jJCda ef JSYI HMhK GbJUGOjI bOeJ deDJeQGJ YdejI OGNd GdbWQ hNGQLg hMdbGJ fbGTjI aj ehGSe hefGSHGJ eNJdaI(B. (3gPg GdHMhK aj GdMbjbI JJCda Mhd eMhQ hGMO hjYQVge cGdJGdj (B: (3GdebOeI(B-(3GdHGH GdChd (B: (3GdYhdeI (B.. (3CHYGOgG hSHd ehGLgJgG (B: (3GdaUd GdChd (B: (3GdJCUjd GdeaGgjej hGdJCQjNj ddYhdeI (B: (3ChdG (B: (3GdJCUjd GdeaGgjej ddYhdeI (B: (3GdaUd GdKGfj (B: (3GdYhdeI GdEbJUGOjI hGdCHYGO GdfGLeI YfgG aj GdHdOGf GdfGejI (B: (3GdYhdeI GdEbJUGOjI (B: (3GdaUd GdKGdK (B: (3eBRb GdYhdeI hSHd ehGLgJgG (B: (3eCRb GdYhdeI (B: (3SHd ehGLgI GdYhdeI(B-(3GdHGH GdKGfj (B: (3eSjQI GdYhdeI fMh GdgjefI (B: (3GdaUd GdChd (B: (3GdYhdeI GdeGVj UhQI GdMGVQ (B: (3GdaUd GdKGfj (B: (3GdYhdeI Jcjja acQj deRjO ef GdgjefI (B: (3GdaUd GdKGdK (B: (3YhdeI GdfaW (B: (3ChdG(B: (3CgejI GdfaW GdYQHj HGdfSHI ddhdGjGJ GdeJMOI GdCeQjcjI (B: (3KGfjG (B: (3GdhVY GdfaWj ddOhd GdUfGYjI (B: (3GdaUd GdQGHY (B: (3EbJUGO GdShb GdETJQGcj (B((3GdJLQHI GGdUjfjI (B) :(3ChdG(B: (3Gdehba ef GdedcjIghehba acQj (B: (3KGfjG(B: (3GdJWhQGJ lGJUGOjI aj GdUjf efP (B1949 (3hdMO GdCf (B: (3GdaUd GdNGeS (B: (3CHYGO eTQhY GdYbhHGJ GdGfcdhCeQjcjI (B"(3OQGSI aj GdGbJUGO GdSjGSj ddMUGQ GdTGed (B" : (3GdaUd GdSGOS (B: (3GdYhdeI hGdEMJdGd GdCeQjcj ddYQGb (B: (3ChdG (B: (3GdJCUjd GdJGQjNj ddefXheI GdQCSeGdjI (B: (3KGfjG(B: (3CReI GdfXGe GdQCSeGdj (B: (3MbjbI GdYhdeI GdCeQjcjIs
(3HjHdjhZQGajG U(B.143s
Keywords: (3GbJUGO YGdejs; (3GbJUGO eGdjs; (3YhdeIs